Pengaruh Perilaku Konsumtif, Literasi Keuangan dan Teman Sebaya terhadap Perilaku Menabung Mahasiswa Aktif Angkatan 2021 FEBI UNZAH - Ula, Ummi Mauliatul; Nuntufa; Norhayati (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
The research intends to investigate the influence of consumptive behavior, financial literacy, and peers on the saving behavior of active students of batch two thousand two one of the Faculty of Economics and Islamic Business, UNZAH. Employing a quantitative method with a causal associative research, the study examines the relationship among multiple variables. Data was gathered via questionnaire distributed to 136 students selected through the method of saturated sampling. Multiple linear regression was applied for the analytical method, involving instrument test, classical assumption test, T test, F test, and R2 utilizing the IBM SPSS 26. Findings suggest that partially, a significant negative impact was found on the relation of consumptive behavior and saving behavior, while a significant positive impact was found on the financial literacy as well as peers with student saving habit. Simultaneously, the three independent variables have a big impact on saving behavior with a determination value of sixty-eight, eight percent, which means that sixty-eight, eight percent of the saving behavior variation can be interpreted by these three variables.